EXPLORING THE HOUSING POLICY FACTORS ON THE RELATIONSHIP BETWEEN SOCIO-ECONOMIC AND DEMOGRAPHIC AND IMMIGRANTS’ HOMEOWNERSHIP - Sarimah Awang; Gazi Nurul Islam; Bajoyai Bardai (International Conference on Social and Islamic Studies, 2021)
The rules and regulations for the immigrant’s homeownership has become among important policy issue. Housing policy in Brunei has changed over the past decades. The immigrants contribute to the economic growth of the country for a number of decades.  The objective of the study was to examine the effects of housing policy on the homeownership among the different status of immigrants.  Housing accessibility, housing subsidy, housing design and housing policy change were factors of housing policy in the study.  Primary method using survey questionnaire was employed as data collection.  The sampling technique composed of snowballing which were later stratified and cluster in a random manner. The study focuses on third generation immigrants residing permanently in Brunei.  In this study, 400 questionnaires were useable, which satisfies the requirement of adequate sample size and the minimum sample size for SEM.  The data were keyed in, coded and analysed using SPSS, SEM and Sobel test.  The result of the regression analysis shows that p = 0.02, thus the housing policy affects the relationship between socio-economic and demographic; and homeownership of the immigrants. In conclusion, the study confirmed that in order to access homeownership, the immigrants should comply and adhere with the housing policy of a particular country.  The findings of the study contribute to the body of knowledge in homeownership, housing policy, immigrants and the generation of immigrants as well contributes to literatures in migration studies and development studies.